Sozialisation in einer sich wandelnden Medienumgebung Zur Rolle der kommunikativen Figuration Familie - Kammerl, Rudolf; Lampert, Claudia; Müller, Jane (Medienpädagogik, 2022)
As a result of mediatisation, the conditions under which children form relationships with others and position themselves within different social contexts are changing. Media developments and the increasing use of the media in families, peer groups, schools etc. are affecting the constellations of actors and communicative practices within these social contexts and are contributing to blurring the boundaries between them. The qualitative longitudinal study of children between six and twelve and their parents that is examined in this book focuses on the role of media-related negotiation processes and their relevance for social positioning over time. The book's starting point is the family as the first and most important station in the process of socialisation. With contributions by Andreas Dertinger, Rudolf Kammerl, Claudia Lampert, Jane Müller, Paul Petschner, Katrin Potzel and Marcel Rechlitz.